Fundamentals of Sexually Transmitted Infections 2017
DOI: 10.5772/intechopen.68927
|View full text |Cite
|
Sign up to set email alerts
|

Microbicides for the Prevention of HPV, HIV-1, and HSV-2: Sexually Transmitted Viral Infections

Abstract: Sexually transmited diseases (STDs) can be transmited through genital-genital, orogenital, or anogenital contacts and remain to be a public health concern worldwide. Approximately one million people around the world are believed to be newly infected with sexually transmited infections (STIs) each day. Numerous causative agents including bacteria, viruses, protozoa, yeast, and fungi are responsible for STIs; however, viruses exhibit more serious risks, probabilities and outcomes of STDs than other organisms. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 121 publications
0
2
0
Order By: Relevance
“…10 Following the result of the phase 2 clinical trials in Africa, Nonoxynol-9 was found to offer no protection against HIV and actually increased the risk of genital disease. 102 …”
Section: Resultsmentioning
confidence: 99%
“…10 Following the result of the phase 2 clinical trials in Africa, Nonoxynol-9 was found to offer no protection against HIV and actually increased the risk of genital disease. 102 …”
Section: Resultsmentioning
confidence: 99%
“…Each year, more than 400000 new cases are reported worldwide, and more than 300 women's lives were lost to HPV-related causes in just 2018 [4]. Based on the severity of clinical manifestations, genital HPV types are divided into high-risk as subtypes (16,18,31,33,35,39,45,51,52,56,58,59, 68, 73, 82) associated with premalignant and malignant cervical, penile, vulvar, vaginal, anal, head, and neck cancers; and low-risk such as subtypes (6,11,42,44,51,53,83) that cause warts or benign, highly proliferative lesions on the genitals [5].…”
Section: Introductionmentioning
confidence: 99%